The study and development on Gd2Y(1-x)DyxAl2Ga3O12 phosphor for x-ray detection material. (January 2023) - Kaewnuam, E.; Angnanon, A.; Wantana, N.; Kaewkhao, J.
Abstract: The Gd2 Y(1-x) Dyx Al2 Ga3 O12 phosphors were prepared by the solid state reaction to study in the structure, photon absorption, photo- and radioluminescence properties. The XRD represented a crystalline cubic with Ia 3 ‾ d space group as the main structure of phosphor. The Y atomic sites were fine replaced by Dy in phosphor structure with Dy content (x) in a range of 0.25–1.00. The grain sizes of phosphor samples observed by SEM were in several micrometers. In the absorption spectra, phosphors absorbed the photons with various wavelengths in UV, VIS and NIR region. Both direct Dy 3+ excitation and Gd 3+ →Dy 3+ energy transfer caused the strong photoluminescence (PL) of Dy 3+ around 481 ( 4 F9/2  →  6 H15/2 ) and 582 ( 4 F9/2  →  6 H13/2 ) nm. The PL decay times of phosphors were around 0.10–0.74 ms. Phosphors performed the strong response to X-rays in radioluminescence (RL) spectroscopy which composed of the sharp emission of Dy 3+ ion, broad emission of Y-related complex and weak emission of defects. Phosphor with 0.25 Dy content owned the highest PL and RL intensity of Dy 3+ due to the concentration quenching effect and appropriate lattice constant, while free-Dy phosphor had the highest RL intensity of Y complexes. The Gd2 Y0.75 Dy0.25 Al2 Ga3 O12 phosphors is a promising material for the X-ray detection applications, especially the X-ray imaging screen. Highlights: X-ray detection ability from luminescence of Dy 3+ ion and Y-complex. Photoluminescence of Dy 3+ surrounded by high-symmetry environment in phosphor. Luminescence under the Gd 3+ → Dy 3+ energy transfer. The influence of lattice constant on luminescence properties.